Integrated dynamic analysis of a spar floating wind turbine with a hydraulic drivetrain. (December 2022) - Jiang, Zhiyu; Yang, Limin; Gao, Zhen; Moan, Torgeir
Abstract: Conventional drivetrains with gearbox failures are associated with major downtime in offshore wind turbines. This impacts the maintenance cost and cost of energy. A hydraulic transmission eliminates the need for gearbox and potentially improves the turbine reliability. This paper explores the application of a novel high-pressure transmission machinery to a utility-scale spar floating wind turbine. We present a dynamic model of a hydraulic system consisting of a hydraulic pump, pipelines, a hydraulic motor, and an induction generator. The motor is placed inside the spar platform and operates at a fixed displacement. The hydraulic system is coupled with the aero-hydro-elastic code HAWC2 through an external dynamic link library. The dynamic responses of a 5 MW spar floating wind turbine and a land-based reference wind turbine with this hydraulic system were investigated under various wind and wave conditions. A comparison is made between the characteristics of the two wind turbines under operational conditions and both turbines show decent behaviors, and the statistics of power generation is at the same level compared to that of conventional wind turbines. Through simulation studies, we verify the feasibility and the engineering practice of the proposed hydraulic drive solution to floating wind turbines. Highlights: A novel hydraulic transmission is proposed as an alternative drivetrain. The physical hydraulic system is mathematically represented as ODEs. The ODEs are coupled with an aero-hydro-elastic code. Interesting dynamic characteristics is revealed of the mechanical-structural system. Technical feasibility is demonstrated through simulations under various conditions.